Музыкально-событийные процессы современного академического искусства Крыма в аспекте культурологической регионики - Рикман, К. (Культура народов Причерноморья, 2014)
Статья Музыкально-событийные процессы современного академического искусства Крыма в
аспекте культурологической регионики посвящена презентации современного академического
музыкального творчества в Республике Крым. Кроме того, рассматриваются основные аспекты
событийного анализа, а также анализируются разножанровые сочинения современных крымских
композиторов М.Халитовой (Концерт для оркестра «Ожерелье городов Крыма»), Е.Троценко (Хоровая
«Молитва Ангелу Хранителю»), М.Устинова (Фортепианная прелюдия «Опадающий цвет белого сада») в
контексте музыкальной событийности. Данная статья содержит также обобщённую характеристику
композиторского творчества региона. Стаття Музично-подієві процеси сучасного академічного мистецтва Криму в аспекті
культурологічної регионикі присвячена презентації сучасної академічної музичної творчості в АРКрим.
Розглядаються різножанрові твори в аспекті музично-подієвого аналізу, а також дається узагальнена
характеристика положення композиторської творчості регіону. The article "Musical-Event Processes of Modern Academic Art of the Crimea in Aspect of a
сulturological Regionik" is devoted to presentation of modern academic musical creativity in the Republic of
Crimea. Besides, the main aspects of the event analysis are considered and also are exposed to detailed studying of
the composition of modern Crimean composers who are executed both in the Crimea and in other regions sound
from the central academic platforms.
For a panoramic picture of the Crimean academic musical and composer creativity by the author three composers
writing in a different manner, different genres which creativity has different subject - Merziye Halitovа (A concert
for an orchestra "Necklace of the Cities of the Crimea"), Ekaterina Trotsenko (choral "the Prayer to the Guardian
angel"), Maxim Ustinov (a piano prelude "The falling-down color of a white garden") in the context of a musical
event are chosen.
Merziye Halitovа - rather famous composer having bright, original identity. It has accurate feeling of the form
perfected by composer equipment, her compositions are always by genre defined and have a picturesque national
basis.
Maxim Ustinov treats "younger generation" of the Crimean composers. It works in different genres, among which
piano, chamber, symphonic, vocal and choral music.
The basis of creativity of E.Trotsenko is made by musical and theatrical, the church music and choral works.
The considered works are indicative for a modern situation in the academic composer creativity of the Crimea,
however don't settle subject, stylistics, means of expression and a circle of images of the compositions presented in
the Republic of Crimea.
Promotion of regional composer schools is the necessary factor strengthening domestic culture in general.